Anaysis of the public participation process in the gauteng etolls initiative - De Freitas, Manuel Simão França (My University, 2021)
This study analyses the public participation processes led by SANRAL (South African National Roads Agency Limited) within the Gauteng Freeway Improvement Project (GFIP). The public appeared to have been against this project from the beginning claiming that they were not properly consulted on this project. The term public is defined by the Merriam-Webster dictionary “as a group of people having common interests or characteristics”. The common interest in this study was the etolls initiative.
A research report submitted in 50% fulfilment of the requirements for the degree Master of Management in Governance and Political Leaderships to the Faculty of Commerce, Law and Management, School of Governance, University of the Witwatersrand, Johannesburg, 2021
Keywords: Transportation; SANRAL (South African National Roads Agency Limited); E-toll; Gauteng; SDG-3: Good health and well-being